FIRST STEP VIEW OF THE EFFICACY OF ANTINEOPLASTIC AGENTS - Yu, Da; Wu, Jinmin (Chinese Journal of Cancer Research, 2013)
A hmnon K562 leukaemia cell line and acute adult leukaemia patient samples have been used to test the efficacy of antineoplastic agents with MTT assay. All 18 drugs were invoved. According to the pro-pose of experiment these drugs were applied at different apporttmities or combinations. The drug efficacy has been observed and summarized as foredifferent conditions: 1. The change of the time (ΔT) closely related with drug effacacy, during the duration the change of drug concentration (ΔC) at certain extent has almost no influence; 2. The ΔC closely related with the efficacy, the ΔT has no infhamce; 3. The ΔC and ΔT effect the results together; and 4. The ΔC and ΔT effect not the result. And then draw a conclution that the process of drug effacacy has a multiple function with flat district.